REDUCING GAS-PHASE FIRING OF OXIDIZED NICKEL ORE IN FERRONICKEL PRODUCTION - Мельник, Сергій; Приходько, Сергій; Акреєв, Володимир; Овчарук, Анатолій (SWorldJournal, 2025)
Gas-phase reduction firing is a process of high-temperature treatment of materials in the furnaces with atmosphere saturated with reducing gases. A limited amount of oxygen leads to the reduction of metals and other compounds, changing the structure and p